Development of Problem-Solving-Based Digital Learning Media for Flat-Sided 3D Geometry in Junior High School - Aditya, Pandu; Hiltrimartin, Cecli (JTAM (Jurnal Teori dan Aplikasi Matematika), 2024)
Mastery of concepts is necessary for students in learning geometry, particularly in the topic of flat-sided 3D spatial structures. A strong grasp of concepts is achieved through non-routine problem-solving exercises, which are an integral part of problem-solving-based learning. According to the OECD (Organisation for Economic Co-operation and Development) of Education and Skills 2030, problem-solving-based learning is considered an important component in the curriculum of 60% of countries worldwide. The use of digital media is an innovative approach in education that can transform abstract geometric forms into real-world situations. The focus of this research is to develop digital media to enhance conceptual understanding among eighth-grade students at Yosowinangun Junior High School. The outcome of this study is a valid, practical, and effective digital learning medium for improving conceptual understanding. The research adopts the ADDIE model as the methodological framework. The research sample consists of twenty eighth-grade students. Data collection instruments include validation sheets, practicality questionnaires, interviews, and tests. The research findings indicate that the learning media is valid based on the analyzed validation sheets. Furthermore, the learning media is considered practical based on student response questionnaires, with an average score of 83.3%. The learning media also has a potential effect on conceptual understanding, as evidenced by the overall test results falling into the good category with an average score of 74.75%. Therefore, problem-solving-based digital learning media becomes an effective tool to assist students in developing their conceptual understanding in the process of learning flat-sided 3D spatial structures in geometry.